Belajar Sejarah Islam Masuk Indonesia dengan Game Berbasis Multiplatform - Imam Nurrahim, Dian; , Endah Sudarmilah S.T., M.Eng (2016)
Game is a fun game, not a few children who are addicted to the game. With the existence of several theories about the coming of Islam to Indonesia, among others, Gujarat theory, the theory of Makkah, and then to the Persian theory the author will make an educational game based multiplatform use application construct 2 with rewards that explains these theories. The purpose of this study to draw the attention of elementary school students to help beajar material Islamic history Log Indonesia. This study uses SDLC (systems development life cycle) comprising the steps of a plan (planning), analysis (analysis), design (design), implementation (implementation), testing (testing), and management (maintenace). The results of this study are the games with the material history of Islam Sign Indonesia that can be played on desktop and smartphones.